Determination of the water quality of the Chancay-Baños river using aquatic macroinvertebrates. - Atoche-Bazán, Leslie; Cordova-Rojas, Carlos; Ramos-Camacho, Anderson; Sánchez-Llanos, Sergio; Velezmoro-Cruzado, Katherine; Sanchez-Peña, Marco (LACCEI, 2024)
The objective of the research was to analyze the water quality in the ChancayBaños river applying aquatic macroinvertebrates and biotic indices, taking into account physicochemical parameters (pH, conductivity, temperature, dissolved oxygen, TDS, salinity), as well as the list of benthic macroinvertebrates identified for the application of biotic environmental quality indices (BMWP/Col and EPT), in addition to the Shannon and Simpson diversity indices. In addition, to obtain the list of plants identified at the sampling stations and the application of the IHF and QBR indices, considering all the data obtained from both campaigns. For the investigation, two samples were carried out, one in dry season and the other in rainy season, collecting a total of 16 samples in which the identification of macroinvertebrates present in the body of water was applied. Thus, a descriptive study was carried out, with results such as a pH whose average value is 7.2 and a maximum of 8.88 in E-7 at the dry season; the highest conductivity concentration was given for station E-1 with 365 μS/cm; of all the samples an average salinity of 0.095 and temperature of 23.7°C was obtained. For the TDS the maximum and minimum values were found in E-1, considering both campaigns. On the other hand, the indices IHF and QBR establish that the quality of the riverbank is of intermediate quality or in some stations of strong alteration, while the description of the fluvial habitat is in the ranges of habitat with some limitations and adequate hábitat.Additionally, the EPT and BMWP/col indices obtained values that were classified as poor water quality with contamination in the critical and very critical range. Concluding that, if there is a relationship between the results of the physicochemical parameters, benthic macroinvertebrates, biotic and diversity indices with the quality of the ChancayBaños river.